1993
DOI: 10.1172/jci116624
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of the rabbit cortical collecting duct from obstructed and contralateral kidneys after unilateral ureteral obstruction.

Abstract: IntroductionElectrophysiological techniques were used to determine the electrical properties of the collecting duct (CD) cell in the isolated cortical collecting duct from obstructed (UUOOK) and contralateral (UUOcK) kidneys in rabbits 24 h after unilateral ureteral obstruction (UUO); results were compared with those from sham-operated kidneys. The lumen-negative transepitheHal voltage and the basolateral membrane voltage (V B) were decreased in the UUOOK, and increased in the UUOCK. The transepithelial conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
25
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 53 publications
8
25
0
Order By: Relevance
“…Slices of the coronal section 1-2-mm thick from left kidneys were made and transferred to a dish containing a cold intracellular fluid-like solution of the following composition (mM): 14 KCl, 44 K2HPO4, 14 KH2PO4, 9 NaHCO3, and 160 sucrose. As described previously (20)(21)(22)(23)(24)(25)(26)(27), this dissection medium was selected because it has been reported that intracellular fluid-like solutions are much better at preserving kidney tissue, metabolically as well as functionally. Segments of CCDs were dissected from the cortex and transferred to a bath mounted on an inverted microscope (Diaphot; Nikon, Tokyo, Japan).…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…Slices of the coronal section 1-2-mm thick from left kidneys were made and transferred to a dish containing a cold intracellular fluid-like solution of the following composition (mM): 14 KCl, 44 K2HPO4, 14 KH2PO4, 9 NaHCO3, and 160 sucrose. As described previously (20)(21)(22)(23)(24)(25)(26)(27), this dissection medium was selected because it has been reported that intracellular fluid-like solutions are much better at preserving kidney tissue, metabolically as well as functionally. Segments of CCDs were dissected from the cortex and transferred to a bath mounted on an inverted microscope (Diaphot; Nikon, Tokyo, Japan).…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%
“…Segments of CCDs were dissected from the cortex and transferred to a bath mounted on an inverted microscope (Diaphot; Nikon, Tokyo, Japan). Each tubule was perfused in vitro according to the techniques developed by Burg et al (31) and as modified in this laboratory for the use of intracellular microelectrodes (20)(21)(22)(23)(24)(25)(26)(27). Since the details of the technique have been published previously (20)(21)(22)(23)(24)(25)(26)(27), they will be presented here only briefly.…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations